Networks and spatial structure, their role in development - Huamantinco Araujo, Alicia (2017)
Peru’s insertion, at different times in its history, in the world’s economy as exporter of raw materials had been materializing in its territory through the establishment of the technical networks. Due to their close relationship with the physical characteristics of the territory, the circulation networks have played a key role in the differentiation of the spaces at the national level, making locations accessible and articulated or otherwise marginalized. Nowadays, when the global modernization model is based on technology and knowledge and the States and regions worry about being isolated, it is essential to reflect over the challenge that represents for regional development the fact that the country’s transport system –railways and highways– was build not with the objetive to develop the economy of the regions but, fundamentally, to articulate the sources of raw material with the end markets, the regions with the hegemonic centers.